Pulsating multiple nano-jet impingement cooling system design by using different nanofluids for photovoltaic (PV) thermal management. (January 2023) - Maatoug, Samah; Moulahi, Ali; Bazuhair, Naseem; Alqarni, Shatha; Selimefendigil, Fatih; Aich, Walid; Kolsi, Lioua; Mhimid, Abdallah
Abstract: The present work proposes a new cooling system for thermal management and cooling of photovoltaic (PV) systems. Pulsating flow with multiple jet impingement is considered by using different fluid types. Hybrid nanofluid and alumina–water nanofluid having cylindrical ans spherical shaped nanoparticles are used as the cooling medium. The study is conducted by using finite volume method for various values of pulsating amplitude (between 0 and 1), Strouhal number (between 0.01 and 1), solid volume fraction of nanoparticles (between 0 and 2%) and slot number of the impinging jet (between 1 and 13). It is observed that pulsating amplitude is more effective on the cooling performance enhancement as compared to frequency while average Nusselt number (Nu) rises by about 63.5% while temperature drop of 2.16 °C can be achieved when pulsation amplitude is increased from 0 to 1. Nanofluid with cylindrical shaped nanoparticles and hybrid nanofluid show very similar trends while temperature drop of 2.6 °C is achieved when cooling system with nanofluid-cylinder in pulsating flow case is compared with pure-fluid in non-pulsating flow configuration. When nanoparticles loading amount on the thermal improvement is compared, the most favorable cases are obtained for nanofluid-cylinder and hybrid nanofluid case. The average Nu increments become 3.5%, 22.8% and 22.9% for nanofluid-spherical, nanofluid-cylinder and hybrid nanofluid when lowest and highest nanoparticle loading amount cases are compared. Increasing the slot number in pulsating flow case significantly rises the Nu and drops the average panel surface temperature. When different systems are compared pulsating nano-jets cooling system using alumina–water nanofluid with cylindrical shaped nanoparticles provides the most effective cooling system while while temperature drop of Δ T = 37 . 30 °C is achieved at the highest amplitude and highest loading of nanoparticles in the pure fluid as compared to uncooled PV system.